Career anchors reimagined finding direction and opportunity in the changing world of work - Schein, Edgar H.; Van Maanen, John; Schein, Peter A. (Ascent Audio, 2023)
In the newly revised edition of Career Anchors: Finding Direction and Opportunity in the Changing World of Work, a team of world-renowned management and culture experts delivers a uniquely insightful exploration of your own career values and work relationships as they relate to your past and future choices. This easy-to-use workbook in combination with an online self-assessment offers critical and accessible self-diagnostic exercises along with information about the changing career scene and new descriptions of the eight career anchor categories. This book will help you: explore how your work choices now relate to your family and self-development; explore how the rapidly changing world of work and business emphasizes globalization, competition, technology, organizational instability, uncertainty, and shifting values; engage in a powerful relationship mapping process that helps you to consider how your work and career choices now interact with your relationships with family, friends, and community; and review the career anchor values and examine how these values have changed, so you can make better choices of what, when, where, and how to work as you look ahead. This newest edition of Career Anchors is a can't-miss resource written to help you analyze, assess, and understand the past, present, and future of your own career.